Performance Improvement of Pumps Fed by the Variable Speed Drives - Vodovozov, Valery; Bakman, Ilja (Electrical, Control and Communication Engineering, 2013)
Speed inaccuracy decreases the pump efficiency, reliability, and energy saving. This research is devoted to the determination of the ways of accurate speed control of the pump drives operated under changeable loads. The impact of speed inaccuracy on the pump performance is studied. Based on the analysis of methods for the static accuracy improvement, the drawbacks of the traditional approaches have been shown with reference to the pumping applications. A new methodology of the slip compensation has been proposed for implementation to improve the scalar drive performance. It notably decreases the speed inaccuracy of the open-ended pumping applications. The enhanced quality of the drive control at different loading conditions has been shown on a laboratory test bench. Also, for the multi-pump systems this approach results in an additional benefit from the viewpoint of the operation around the best operation point providing a safe pump control both to exclude the pump damage and to improve the process quality.